Primitive of x by Hyperbolic Cosine of a x

From ProofWiki
Jump to navigation Jump to search

Theorem

$\displaystyle \int x \cosh a x \rd x = \frac {x \sinh a x} a - \frac {\cosh a x} {a^2} + C$

where $C$ is an arbitrary constant.


Proof

With a view to expressing the primitive in the form:

$\displaystyle \int u \frac {\d v} {\d x} \rd x = u v - \int v \frac {\rd u} {\rd x} \rd x$

let:

\(\displaystyle u\) \(=\) \(\displaystyle x\)
\(\displaystyle \leadsto \ \ \) \(\displaystyle \frac {\d u} {\d x}\) \(=\) \(\displaystyle 1\) Derivative of Identity Function


and let:

\(\displaystyle \frac {\d v} {\d x}\) \(=\) \(\displaystyle \sinh a x\)
\(\displaystyle \leadsto \ \ \) \(\displaystyle v\) \(=\) \(\displaystyle \frac {\sinh a x} a\) Primitive of $\cosh a x$


Then:

\(\displaystyle \int x \cosh a x \rd x\) \(=\) \(\displaystyle x \paren {\frac {\sinh a x} a} - \int \paren {\frac {\sinh a x} a} \times 1 \rd x + C\) Integration by Parts
\(\displaystyle \) \(=\) \(\displaystyle \frac {x \sinh a x} a - \frac 1 a \int \sinh a x \rd x + C\) Linear Combination of Integrals
\(\displaystyle \) \(=\) \(\displaystyle \frac {x \sinh a x} a - \frac 1 a \paren {\frac {\cosh a x} a} + C\) Primitive of $\sinh a x$
\(\displaystyle \) \(=\) \(\displaystyle \frac {x \sinh a x} a - \frac {\cosh a x} {a^2} + C\) simplification

$\blacksquare$

Also see


Sources